Study on the possible role of the -174G>C IL-6 promoter polymorphism in predicting response to rituximab in rheumatoid arthritis - F. Fischetti; L.M. Bambara; A. Carletto; M. Cutolo; P. Sarzi-Puttini; R. Pellerito; C. Fabro; E. Pontarini; M.A. Cimmino; P. Morassi; F. Atzeni; M. Saracco; et al. (PAGEPress Publications, 2011)
Several studies demonstrated the efficacy of the B-cell depletion therapy with rituximab (RTX) in RA patients, including those unresponsive to anti- TNF therapy, underlying the important role of B cells in this disease (1-5). Several recent papers have demonstrated a differential effects of RTX in depleting B-cells and blocking plasma cell generation at the synovial and at the bone marrow level (7-9). This differential effect may explain why among patients who respond to RTX, some relapse while others show a very prolonged response, independently from the reappearance of B-cells in the peripheral blood (6). However, the efficacy of RTX may also depend on the individual genetic predisposition. At this regard, very few data were produced by now.